A New Crystalline Ketoprofen Sodium Salt: Solid-State Characterization, Solubility, and Stability - de Oliveira Junior, Homero; Borges, Bruno Arantes; Barbosa, Thulio Wliandon Lemos [UNESP]; Batista, Ataislaine; Braga, Maria Teresa Leite; de Araújo, Magali Benjamim; Bonfilio, Rudy (Elsevier, 2021)
Ketoprofen (KTP) is an Active Pharmaceutical Ingredient (API) that has low solubility in aqueous solvents. The use of KTP salts has attracted attention due to its improvements in terms of solubility, tolerability, higher rate and extent of absorption, and faster onset of the therapeutic effect. In this work, a crystalline KTP sodium salt (coded as KTP-Na) was successfully obtained and widely characterized by X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), solubility and accelerated stability studies. XRD results showed that KTP-Na is not yet reported in the literature. Moreover, FTIR, DSC and TGA were useful for differentiation of KTP-Na from the KTP commercialized form (coded as KTP-R1). The solubility of KTP-Na in water was about 80 times greater than the KTP-R1. However, KTP-Na showed lower physical stability in storage conditions at 40 ± 2°C/ 75% ± 5% RH when compared to KTP-R1, which was shown to be related to a high hygroscopicity of KTP-Na. Therefore, due to its higher solubility, KTP-Na may be a viable alternative for use in solid dosage forms. However, the presence of moisture must be strictly controlled to avoid water absorption and consequent amorphization.
Keywords: Fourier transform infrared spectroscopy; Ketoprofen sodium; Solid-state characterization; Solubility; Stability; Thermal analysis; X-ray powder diffraction